SCIENTIST OF THE FUTURE: AN EXAMINATION OF THE CAREER CHOICES AND INTERESTS OF GIFTED AND TALENTED STUDENTS IN THE FIELD OF PHARMACEUTICAL SCIENCE - Menon, Premanarayani (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Gifted education provides enrichment and accelerated programs to support high-ability students in their continuous advancement. It is essential for educators to investigate the passions of intellectually advanced students in a particular area to provide top-notch learning experiences. The worldwide COVID-19 emergency requires a rise in the number of pharmaceutical scientists to develop and produce new medications to address the current pandemic and upcoming health issues. This study seeks to investigate the curiosity of intellectually advanced and talented students in the field of pharmaceutical science. A survey was conducted to collect quantitative data from 322 high school students at the PERMATA@Pintar National Gifted Center, located at the National University of Malaysia, who are in grades 8-12. Normality tests (Shapiro-Wilk test and Kolmogorov-Smirnov test) indicated that the data did not follow a normal distribution. As a result, non-parametric analyses were conducted, such as the Mann-Whitney U test, Kruskal-Wallis H test, and logistic regression. The results showed that students' interest in the pharmaceutical science field was correlated with their likelihood of pursuing careers related to pharmaceutical science. The discovery also highlighted the variation in students' interests based on gender. Overall, female students showed greater interest in the pharmaceutical science field compared to male students. These findings suggest a need to enhance the visibility of the pharmaceutical field in order to develop innovative solutions for global health challenges.